Pemahaman Konsep Matematis Siswa Menggunakan Model Pembelajaran Cooperative Integrated Reading and Compositions (CIRC) - Ramadhani, Nurul; Isnaniah, Isnaniah; Imamuddin, M; Rusdi, Rusdi (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study was motivated by the problem identified in Grade VIII of SMP Negeri 2 2x11 Kayutanam, namely the low level of students’ mathematical conceptual understanding. This issue was attributed to teacher-centered instructional practices and the limited variation in teaching models implemented in the classroom. One proposed solution to address this problem was the application of a cooperative learning model, namely Cooperative Integrated Reading and Composition (CIRC). The objective of this study was to determine whether students’ mathematical conceptual understanding taught using the CIRC model was better than that of students taught through conventional instruction in Grade VIII of SMP Negeri 2 Kayutanam. This research employed a quantitative approach with a pre-experimental design using the Static Group Comparison Design, in which data were analyzed using inferential statistics to examine differences in mathematical conceptual understanding between the experimental and control groups. The population of this study consisted of all Grade VIII students of SMP Negeri 2 Kayutanam. The sample included Class VIII.1 as the experimental group and Class VIII.3 as the control group. The research instrument used was an essay test designed to measure students’ mathematical conceptual understanding. Based on data analysis using the t-test, it can be concluded that students’ mathematical conceptual understanding taught through the Cooperative Integrated Reading and Composition (CIRC) model was better than that of students taught through conventional learning in Grade VIII of SMP Negeri 2 2x11 Kayutanam.”